(untitled) (Physical Education, Health and Social Sciences, 2025)
Background and Introduction: Non-alcoholic fatty liver disease (NAFLD) has been demonstrated that insulin resistance and metabolic syndrome are associated with non-alcoholic fatty liver disease (NAFLD), a prevalent condition in the general population. The elderly population has higher rates of certain metabolic syndrome components. The current study set out to ascertain the clinical manifestation of non-alcoholic fatty liver disease (NAFLD) in the elderly, as well as its relationship to underlying metabolic abnormalities. Objective: The objective of our study is to find out the grading of fatty liver disease in non-obese elderly patients on ultrasound. Materials and Method: A total of 50 cooperative responding patients were included and the study was carried out in AL-Jannat Raza Clinic Jalalpur. Results: The study of Grading of fatty liver in non-obese patient is held on Al- Jannat Raza clinic, Jalal purpirwala for duration of about 3 months which describes the grading of fatty liver and the age factor with their lifestyle is correlated as middle aged the metabolic condition often manifest or worsen during this stage of life. Fatty liver grades distribution among 50 participants. Grade 1 fatty liver was observed in 30% of participants, Grade 2 in 44% , and Grade 3 in 26%.On ultrasound, there is mild increase in echogenicity of liver on grade 1 fatty liver There is moderate increase in echogenicity of liver with obscured vessels in grade 2 and Severe increase in echogenicity with poor diaphragm in grade 3. Conclusion: Our study concludes that fatty livers in nonalcoholic non obese patients are associated with insulin resistant and metabolic problems. The age distribution of 50 participants aged between 50 and 60 years. It shows the frequency, percentage, valid percentage, and cumulative percentage for each specific age. The most common ages were 53 and 54 years in the sample. All data are valid with no missing value. The gender distribution of the 50 participants. Among them,19 was male and 31 were female. The distribution of fatty liver grades among 50 participants. Grade 1 fatty liver was observed in 15 of participants, Grade 2 in 22, and Grade 3 in 13. Grade 2 fatty liver was common, observed in 22 participants.